PERTUMBUHAN DAN HASIL PAPRIKA (Capsicum annuum var-grossum) PADA BEBERAPA JENIS NAUNGAN - Tulung, Stella M.T.; Demmassabu, Sofia (EUGENIA, 2011)
ABSTRACT   The objective of this research is to detect the influence of shade kinds to the  growth and yield of paprika and the suitable kinds of shades for paprika. Varieties Yolo Wonder was applied in this research and the research was located at Kakaskasen III, Kecamatan Tomohon Utara for four months.  The research was carried on through Randomized Group Design by using three types of treatments and six replicates.  The treatments were as follows:  without shade, using transparent plastic shade and  using stubble of paddy shade. Detected variable included: the height of the plant, leaf area, amount of the fruit, length, diametre and the weight of the fruit. The height of the plant measured every week since two weeks after planting  and the leaf area was measured according to the height of the plant. The amount, lenght, diametre and the weight of the fruit measured during the harvest time. The result of the research shows that diffrerent kinds of shades brings different influence to the growth and yield of paprika and the research shows that the suitable shade for the growth and yield of paprika is transparent plastic shade. Keyword: paprika, shade